2020
DOI: 10.1038/s41598-020-66345-7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of os cordis in the cardiac skeleton of chimpanzees (Pan troglodytes)

Abstract: Cardiovascular diseases, especially idiopathic myocardial fibrosis, is one of the most significant causes of morbidity and mortality in captive great apes. This study compared the structure and morphology of 16 hearts from chimpanzees (Pan troglodytes) which were either healthy or affected by myocardial fibrosis using X-ray microtomography. In four hearts, a single, hyperdense structure was detected within the right fibrous trigone of the cardiac skeleton. High resolution scans and histopathology revealed trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 54 publications
0
27
0
1
Order By: Relevance
“…In adult otters [45] and various ungulates such as buffalo [46], white rhinoceros [47] and sheep [48], a "heart bone" is present in the fibrous trigone between left AV canal and aorta. A subgroup of diseased chimpanzees with myocardial fibrosis presented with trabecular bone or hyaline cartilage in the right fibrous trigone [49]. In (sub)adult alligators, a cartilage crown is present, nearly completely encircling the roots of both aortas [50,51], but penetrating not as deep into the ventricle as described by us.…”
Section: Cartilage In the Oft Cushionsmentioning
confidence: 55%
“…In adult otters [45] and various ungulates such as buffalo [46], white rhinoceros [47] and sheep [48], a "heart bone" is present in the fibrous trigone between left AV canal and aorta. A subgroup of diseased chimpanzees with myocardial fibrosis presented with trabecular bone or hyaline cartilage in the right fibrous trigone [49]. In (sub)adult alligators, a cartilage crown is present, nearly completely encircling the roots of both aortas [50,51], but penetrating not as deep into the ventricle as described by us.…”
Section: Cartilage In the Oft Cushionsmentioning
confidence: 55%
“…In adult otters [46] and various ungulates such as buffalo [47], white rhinoceros [48] and sheep [49], a 'heart bone' is present in the fibrous trigone between left AV canal and aorta. A + subgroup of diseased chimpanzees with myocardial fibrosis presented with trabecular bone or hyaline cartilage in the right fibrous trigone [50]. In (sub)adult alligators a cartilage crown is present nearly completely encircling the roots of both aortas [20,51]), but penetrating not as deep into the ventricle as described by us.…”
Section: Outflow Tract Separationmentioning
confidence: 63%
“…In the present study, pathological changes were not observed in the ossa cordis/cartilage cordis. Previous reports on the ossa cordis in chimpanzees revealed that its formation was related to pathological changes [ 14 ]. In this case, an increased collagen level was observed, which was adjacent to the ossa cordis/cartilage cordis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] proposed new functions of the cartilaginous foci in Syrian hamster hearts as pivots resisting the mechanical tensions of cardiac motion. However, it was reported that heart disease may also be associated with the development of ossa cordis, as observed for idiopathic myocardial fibrosis in chimpanzees [ 14 ]. Marine mammals include nonlanding species (i.e., cetaceans) and landing species (i.e., pinnipeds), and their cardiac workloads may be different.…”
mentioning
confidence: 99%